Equilateral triangular patch antenna for UHF RFID applications. Issue 5 (18th March 2014) - Yeh, C. H.; Hsu, Y. W.; Sim, C. Y. D.
ABSTRACT This article proposes an equilateral triangule‐shaped patch antenna for radio frequency identification (RFID) applications in the 900 MHz (902–928 MHz) ultra high frequency (UHF) band. To achieve optimal impedance matching and 10‐dB operating bandwidth at the desired band, the L‐shaped probe‐feed technique was used as the feeding structure of the proposed antenna. Furthermore, a near semicircular notch was also loaded into the patch so that good circularly polarized (CP) radiation can be generated from the proposed patch antenna. By simply shifting the position or radius of this notch, the CP frequency can be varied with ease. Here, 10‐dB impedance bandwidth and 3‐dB axial ratio bandwidth of 25 and 3% were achieved. Furthermore, stable gain variation of approximately 6 dBi was also exhibited across the RFID UHF band. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:580–586, 2014.